PARADOKS DAN IMPLIKASINYA DALAM HUMOR BERTEMA KORUPSI - Ai Kurniati (Balai Bahasa Kalimantan Tengah, 2017)
The corruption-themed humours come along with the increasing number of corruption cases in this country. The uniqueness of paradox in the corruption-themed humours is a contrary opinion or argument to popular opinion could be considered as strange or extraordinary. This paper discusses the form of paradox along with its implications in the corruption-themed humour discourse. This paper aims to describe the form of paradox and its implications in corruption-themed humour discourse. This is a descriptive paper and uses qualitative explanation to elaborate the data. Based on the findings, there are six political humour discourses with the corruption-themed humour which contains paradox language style